Serum levels of cytokines in water buffaloes experimentally infected with Fasciola gigantica - Zhang, Fu-Kai; Guo, Ai-Jiang; Hou, Jun-Ling; Sun, Miao-Miao; Sheng, Zhao-An; Zhang, Xiao-Xuan; Huang, Wei-Yi; Elsheikha, Hany M.; Zhu, Xing-Quan (Elsevier, 2017)
Fasciola gigantica infection in water buffaloes causes significant economic losses especially 27 in developing countries. Although modulation of the host immune response by cytokine 28 neutralization or vaccination is a promising approach to control infection with this parasite, our 29 understanding of cytokine's dynamic during F. gigantica infection is limited. To address this, 30 we quantified the levels of serum cytokines produced in water buffaloes following experimental 31 infection with F. gigantica. Five buffaloes were infected via oral gavage with 500 viable F. 32 gigantica metacercariae and blood samples were collected from buffaloes one week before 33 infection and for 13 consecutive weeks thereafter. The levels of 10 cytokines in serum samples 34 were simultaneously determined using ELISA. F. gigantica failed to elicit the production of 35 various pro-inflammatory cytokines, including interleukin-1β (IL-1β), IL-2, IL-6, IL-12, and 36 IFN-γ. On the other hand, evidence of a Th2 type response was detected, but only early in the 37 course of parasite colonization and included modest increase in the levels of IL-10 and IL-13. 38 The results also revealed suppression of the immune responses as a feature of chronic F. 39 gigantica infection in buffaloes. Taken together, F. gigantica seems to elicit a modest Th2 40 response at early stage of infection in order to downregulate harmful Th1- and Th17-type 41 inflammatory responses in experimentally infected buffaloes. The full extent of anti-F. 42 gigantica immune response and its relation to pathogenesis requires further study.